fo002871: BSP-meeting - Roghes; Hespel, Roger (1950)
"Zwart-witfoto van het bureau op een avondfeest/meeting van de BSP in Gent, rond 1950. V.l.n.r. Gilbert Temmerman, August Balthazar, Henri Lemaire, Edward Anseele jr., Emile Vergeylen, Georges Nachez, Max Buset, Amédée De Keuleneir, Beys en Louis Grau. FULL TEXT AVAILABLE AT AMSAB-ISH"